The insight of the client and the satisfaction in the service - Reyna González, Julissa Elizabeth (2019)
This research presents as a general objective to determine the insight of the client and its relationship with the satisfaction in the taxi service of the company Peru Tours SA, the theories that sustain the present investigation were based on the variables of study, being for insight the Klaric scholar and for satisfaction in the service to Parasuraman. The present investigation responds to a non-experimental design of cross-correlational type, the study sample consisted of 95 frequent clients of the company, to obtain the results non-parametric statistics was used. Hypothesis test and Pearson correlation coefficient, having obtained a moderate correlation of 0.552 among the study variables, for which it is concluded that there is a linear relationship between insight and service satisfaction.